2020
DOI: 10.1038/s41598-020-58461-1
|View full text |Cite
|
Sign up to set email alerts
|

RyR1-targeted drug discovery pipeline integrating FRET-based high-throughput screening and human myofiber dynamic Ca2+ assays

Abstract: Elevated cytoplasmic [Ca 2+ ] is characteristic in severe skeletal and cardiac myopathies, diabetes, and neurodegeneration, and partly results from increased Ca 2+ leak from sarcoplasmic reticulum stores via dysregulated ryanodine receptor (RyR) channels. Consequently, RyR is recognized as a high-value target for drug discovery to treat such pathologies. Using a FRET-based high-throughput screening assay that we previously reported, we identified small-molecule compounds that modulate the skeletal muscle chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 95 publications
3
63
0
Order By: Relevance
“…We solved the throughput problem by developing plate-readers that record FLT data, combining high precision (S/N > 100) and high throughput (>10 samples per s), as needed for HTS [8]. We applied this technology platform, combining biosensor engineering and FLT measurement technology, to disease-relevant protein targets, including SERCA (heart failure, sarcopenia) [7,9], SERCA2a-PLB (heart failure) [13], myosin (heart failure, sarcopenia) [14], myosin-actin (heart failure, sarcopenia) [14,15], ryanodine receptor (heart failure, muscular dystrophy) [16,17], tau (Alzheimer's disease) [18], TNF receptor (inflammation, arthritis) [19,20], and aurora kinase (cancer) [21,22]. In the present study, we describe two extensions of this technology.…”
Section: Introductionmentioning
confidence: 99%
“…We solved the throughput problem by developing plate-readers that record FLT data, combining high precision (S/N > 100) and high throughput (>10 samples per s), as needed for HTS [8]. We applied this technology platform, combining biosensor engineering and FLT measurement technology, to disease-relevant protein targets, including SERCA (heart failure, sarcopenia) [7,9], SERCA2a-PLB (heart failure) [13], myosin (heart failure, sarcopenia) [14], myosin-actin (heart failure, sarcopenia) [14,15], ryanodine receptor (heart failure, muscular dystrophy) [16,17], tau (Alzheimer's disease) [18], TNF receptor (inflammation, arthritis) [19,20], and aurora kinase (cancer) [21,22]. In the present study, we describe two extensions of this technology.…”
Section: Introductionmentioning
confidence: 99%
“…Our results ( Figure 4b) indicate that these compounds may also directly interact with the RyRs, a hypothesis to be explored in future studies. Tacrolimus and Ro 90-7501 had already been identified as RyR regulators in our previous HTS campaigns (via a FRET HTS assay that uses fulllength RyRs), and their RyR activatory and inhibitory effect (respectively) have been reported (20,21 (30 µM), corresponding to the resting and contracting muscle conditions, respectively. This is to glean early insight in the potential effect of a hit on the resting RyR leak, as well as on RyR activation during excitation-contraction coupling.…”
Section: Resultsmentioning
confidence: 99%
“…In that work, fluorescence lifetime (FLT) detection of FRET between the two labeled regulators was used as an assay to identify small-molecule modulators of RyR1. Using this assay, compounds have been identified to decrease RyR1 Ca 2+ leak in skeletal muscle SR membrane vesicles and mechanically skinned muscle fibers (20,21), and were further shown to mitigate force loss in a muscular dystrophy mouse model (22). However, the binding sites of these molecules are difficult to identify within the full-length RyR, which limits progress on understanding their mechanisms of action and hinders structure-activity relationship studies.…”
Section: Introductionmentioning
confidence: 99%
“…For RYR1-RM-affected individuals, a phase 1 clinical trial testing safety of the RyR stabilizing Rycal molecule S48168 (ARM210) is underway (NCT04141670). Moreover, several drugs already approved for other indications are in the clinical trial pipeline for potential repurposing, and novel compounds, identified by highthroughput screening, are being tested in pre-clinical studies [125][126][127]. The recent generation of murine model systems that more closely depict RYR1-RM clinical phenotypes [128,129] and greater understanding of RyR1 structure-function [130] will play a crucial role in identifying RYR1-RM-affected individuals who could benefit most from specific therapeutics.…”
Section: : Completion Of the First Ryr1-rm Natural History Study mentioning
confidence: 99%